Interdisciplinarity for Bridging Disciplines - Pun, Min (Crossing the Border: International Journal of Interdisciplinary Studies, 2017)
Interdisciplinary Studies crosses traditional disciplinary boundaries. No discipline stands alone entirely. In other words, disciplines are not distinct entities at all; they sometimes overlap, sometimes borrow, and sometimes invade upon one another. And some disciplines are famous for their particularly interdisciplinary or bridging disciplines by nature. they may, thus, within the one discipline fuse physical sciences, social sciences and humanities as they consider interrelations between two or more separate domains. Crossing the Border: International Journal of Interdisciplinary Studies Vol.4(1) 2016: 1-2